ANALISIS PERBANDINGAN KINERJA REKSA DANA SAHAM KONVENSIONAL DENGAN SYARIAH PERIODE 2008-2010 - , Nindita Hayuningtyas ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of investing are different for every each of individual, some pursue the gain from speculating and some of them only want to grow their money for the future needs. Basically saving money is not enough to fulfill our needs in the future, itâs because the effect of inflation. Inflation is something that is real and affecting our life, but the fact is many people forgot about the existence of inflation. One of the alternatives in facing the effect of inflation to the value of our money is by investing. This past few years has indicate the massive growth of middle class economy in Indonesia. This can be seen by the level of consumption that are rising for electronic and automotive goods. But unfortunately that massive growth arenât follow by high financial literacy, this cause many individuals trapped in debt only because they want to maintain the lifestyle that they canât afford. The narrowness of their financial literacy make them scare to invest, whereas they have a lot of options if they want to invest. One of the options are through stock mutual funds. The growth of mutual funds in Indonesia is very great. The purpose of this research is to findout whether or not any differences among conventional mutual funds and syariah mutual funds in a time period of 2008-2010. There are 10 samples of mutual funds that represent both conventional and syariah mutual funds equally. The hypothesis of this research were tested using Mann-Whitney and independent sample t-test. Sharpe, Treynor, Jensen, and Sortino are used in calculating the performance of mutual funds. The conclusion of this research is there are no significant difference between the performance of conventional mutual funds and syariah mutual funds.